Meningkatkan Keterampilan Public Speaking melalui Literasi Membaca pada Siswa Kelas 3 SDN Gadingsari Bondowoso - Rizki, Fira Nur; Isfaq, Mochammad Abid Fairuza; Herlambang, Distan Bryan; Saputro, Dendi Ahmad; Wulandari, Shelfi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Education is an important aspect that everyone must pursue. Education is closely related to literacy and speaking. The issues faced by SDN Gadingsari are connected to literacy and speaking. Many students lack confidence and feel shy when speaking in front of the class. Therefore, a social project was created to enhance the public speaking skills of the 3rd-grade students at SDN Gadingsari. This activity is implemented through the provision of materials and direct practice, accompanied by a team of implementers. The team applies a simple approach, starting with introductions, storytelling, learning intonation, to expressing dreams in front of the class. This activity has a positive impact on the students, especially the 3rd graders, who are the main focus of this social project, and it can be beneficial for the students of SDN Gadingsari.